A Critical Discourse Analysis of Media Coverage of Shanghai Students' Performance in the 2009 Program for International Student Assessment. Issue 2 (April 2016) - Huang, Haigen; Placier, Peggy
This study discussed how Shanghai students' performance in the 2009 Program for International Student Assessment was related to its social context. We used a critical discourse analysis approach to identify discourses underlying the students' performance. Our analysis of texts from different sources both in the United States and China revealed that nationalism, knowledge economy, and neoliberalism were major underlying discourses. The study also showed that media reports tended to focus on the comparison of Program for International Student Assessment (PISA) scores of different countries and oversimplified the ranking, which might impede discussions of problems in the educational systems of these countries.